Proceedings of the 9th EAI International Conference on Performance Evaluation Methodologies and Tools 2016
DOI: 10.4108/eai.14-12-2015.2262697
|View full text |Cite
|
Sign up to set email alerts
|

Routing policies for a partially observable two-server queueing system

Abstract: We consider a queueing system controlled by decisions based on partial state information. The motivation for this work stems from road traffic, in which drivers may, or may not, be subscribed to a smartphone application for dynamic route planning.Our model consists of two queues with independent exponential service times, serving two types of jobs. Arrivals occur according to a Poisson process; a fraction α of the jobs (type X) is observable and controllable. At all times the number of X jobs in each queue and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…However, numerical simulations showed that assigning tasks based on SED performed better than SA-JSQ for small system sizes. Ellens et al [22] investigate dynamic routing policies in a local queue system (LHT) with two servers, focusing on scenarios where only a subset of jobs was observable and controllable while others were assigned randomly, showing that heuristic routing strategies can significantly reduce the average response time, closely approaching the performance of the optimal fully observable system under heavy loads, as represented by the SED policy. Their problem is relevant because it shows the strength of a good routine policy.…”
Section: Local Queues With Homogenous (Lh) and Heterogeneous (Lht) Wo...mentioning
confidence: 99%
“…However, numerical simulations showed that assigning tasks based on SED performed better than SA-JSQ for small system sizes. Ellens et al [22] investigate dynamic routing policies in a local queue system (LHT) with two servers, focusing on scenarios where only a subset of jobs was observable and controllable while others were assigned randomly, showing that heuristic routing strategies can significantly reduce the average response time, closely approaching the performance of the optimal fully observable system under heavy loads, as represented by the SED policy. Their problem is relevant because it shows the strength of a good routine policy.…”
Section: Local Queues With Homogenous (Lh) and Heterogeneous (Lht) Wo...mentioning
confidence: 99%